Potret Islamic Studies dan Islam Apologetics (Telaah atas Pandangan Majid Daneshgar tentang Islamic Apologetics) - Afifah, Tsaqifa Aulya (Jurnal Penelitian Ilmu Ushuluddin, 2024)
In the academic environment, learning Islamic Studies gives rise to various polemics and debates. This research will discuss the thoughts of contemporary Muslim figure about Islamic Studies, Majid Daneshgar in his book "Studying the Qur'an in the Muslim Academy." By using descriptive-analytical research methods, the author attempts to explain descriptively what is behind Majid Daneshgar's thoughts on Islamic studies, then the author critically analyzes whether his thoughts are in accordance with the culture of Muslim academic Islamic studies in Indonesia? This research consists of primary and secondary data. Primary data was obtained from the opinions expressed by Daneshgar in his book "Studying the Qur'an in the Muslim Academy," while secondary data was obtained by looking at literature that discussed Majid Daneshgar's thoughts and Islamic Studies. From this research, the author concludes that the tradition of Islamic studies in the academic environment (especially in Indonesia) is not entirely Islamic Apologetics as stated by Majid Daneshgar.